Impact of Financial Literacy on Personal Investment Decisions in Kathmandu Valley (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
In the realm of finance, financial literacy and personal investment decision-making are two important constructs that have been extensively studied. The purpose of this research is to measure the impact of financial literacy on personal investment decisions in Kathmandu valley. A descriptive and causal study was constructed for this study. For the collection of information, structured questionnaires were developed and used in a questionnaire survey. Participants in the stock market made up the study's subjects. According to the convenience sampling approach, 200 samples were collected. Reliability analysis, descriptive statistics, correlation analysis, and regression analysis were all used to comprehensively assess the data. The study found that financial behavior, financial attitude, financial awareness, and financial skill have a significant impact on investment decisions. Policymakers should promote financial literacy and protecting investors can lead to better financial outcomes for individuals and society as a whole.